Zentrale Orte: Zur Karriere und Krise eines Konzepts in Geographie und Raumplanung - Blotevogel, Hans Heinirch (ERDKUNDE, 1996)
This paper deals with the history of central place theory, as conceived by W. CHRISTALLER in 1933, in geography and spatial planning (regional policy and regional planning). On the basis of this retrospective the current importance of central place theory in research and of the central place concept (derived from central place theory) in spatial planning will be discussed. Aided by a five-step arrangement of development phases, the history of central place theory in geography is reconstructed. Amongst others, the belated adoption and the differences of empirical and theoretical research between German-speaking countries and North America will be dealt with. At present central place theory does not play an important role in pure research and is unlikely to do so in the future. Those areas that it was originally devised for now have at their disposal more effective theoretical concepts which are also closer to reality. This holds good for research on retailing as well as for the geography of services and for urban systems research. This discussion is followed by an analogous examination of the rise of the central place concept in (West) German spatial planning. The central place concept was introduced into the definition of objectives of regional planning in the old federal states between 1968 and 1975 and in the new states after the German unification (1990). However, the central place concept has been on the defensive for several years now. The objections brought forward will be identified and reviewed. The refusal of universal validity of the concept is shared here. Nevertheless, the concept is still important today, mainly for two reasons: firstly, it lends itself as an instrument for regulating spatial patterns of developments in the retailing sector, thereby helping to avoid unacceptable developments here. Secondly, it forms an important building stone for the planning of settlement structures which are aligned with the principle of sustainability. Particularly with regard to this context the trend for a far reaching deregulation of spatial planning is highly problematic because a relaxation of objectives and instruments would be a planning and environmental disaster as the long term problems of the environment and of settlement structures necessitate long-term strategies. Regional planning should therefore adhere to the control of spatial developments, yet it should also turn to new practices of an active regional policy in the form of mode rating consensus building political processes and of managing projects.